PENGARUH KOMITMEN TERHADAP KEPUASAN KERJA AUDITOR DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi Empirik Pada Kantor Akuntan Publik di Jawa Tengah) - Achmad Badjuri; Jaeni . (Jurnal Bisnis dan Ekonomi, 2013)
This study will analyze the influence of commitment to the job satisfaction and motivation auditor as an intervening variable. The goal is to test the motivation variable as an intervening variable. Unruk test used to analyze the effect ofcommitment on job satisfaction, namely regression test, test path analysis (path analysis) and also statistical test T. Data were obtained from responses to questionnaires distributed to the auditors who work in public accounting firm in Central Java. The results of the analysis states that the commitment has a positive and significant effect on job satisfaction auditors. Of the test path analysis can be seen that the relationship between organizational commitment and professional commitment is a direct relationship without motivation as an intervening variable. So if the auditor wants improved job satisfaction, then an auditor must have a strong commitment both to the organization and the profession.Keywords: job satisfaction, commitment, motivation